Implementasi Bangunan Ekonomi Islam pada Produk Pembiayaan Mudharabah di Bank Syariah - Trimulato Trimulato (Akademika: Jurnal Keagamaan dan Pendidikan, 2016)
Shariah banking has had a strong legal law in the presence of shariah banking Act number 21 of 2008. The presence of shariah banking in Indonesia are increasingly in demand by the public. Currently the market share of shariah banking has translucent 5%, and the asset side continues to rise well. Shariah banking attached profit and loss sharing system, only financing products in shariah banking still dominated by the sale and purchase murabahah financing. Murabahah financing accounted for 60, 725%. While the contract for the results contribute only 39.275%. Shariah banking are part of Islamic economics can not be separated, so that all the products of shariah banking should be in line with the concept of building an Islamic economy. The aim of research to determine the development of financing in shariah banking and Islamic economics implemtasi building on the product of financing in shariah banking. The results of this paper shows the development of financing products in the development of shariah banking was minimal. With an average growth of only about 3,326%. Thus need support in order to continue to be developed. Products of financing has fulfilled the concept of building an Islamic economy, only one thing that does not fit that assurance requirements specified on the product of financing in Islamic banks, is considered unfair to customers  funds.[Perbankan syariah telah memiliki payung hukum yang kuat dengan hadirnya UU perbankan syariah nomor 21 tahun 2008. Keberadaan bank syariah di indonesia makin diminati oleh masyarkat. Saat ini pangsa pasar bank syariah telah tembus 5 %, dan sisi aset terus meningkat dengan baik. Bank syariah melekat dengan sistem bagi hasil, hanya saja produk pembiayaan di bank syariah masih didominasi oleh pembiayaan jual beli murabahah. Pembiayaan dengan akad murabahah berkontribusi sebesar 60, 725 %. Sedangkan akad bagi hasil hanya berkontribusi 39,275 %. Bank syariah bagian dari ekonomi islam yang tidak bisa dipisahkan, sehingga semua produk bank syariah harus sejalan dengan konsep bangunan ekonomi islam. Tujuan penelitian untuk mengetahui perkembangan pembiayaan mudharabah di bank syariah dan implemtasi bangunan ekonomi islam pada produk pembiayaan mudharabah di bank syariah. Hasil dari tulisan ini menunjukkan adanya perkembangan produk pembiayaan mudharabah di bank syariah perkembangannya sangat minim. Dengan rata-rata pertumbuhan hanya sekitar 3,326 %. Sehingga butuh dukungan agar terus dikembangkan. Produk pembiayaan mudharabah telah memenuhi konsep bangunan ekonomi islam, hanya saja ada satu hal yang tidak sesuai yaitu persyaratan jaminan yang ditetapkan pada produk pembiayaan mudharabah di bank syariah, dianggap tidak adil bagi nasabah pengelolah dana.]